Smoking patterns and outcomes of severe sars-CoV-2 infection: a retrospective cohort study - Branko Beronja; Aleksandra Karan; Biljana Lukic; Ivana Milosevic; Jelena Dotlic; Tatjana Gazibara (Monaldi Archives for Chest Disease)
The purpose of this study was to analyze the association between the number of cigarettes smoked and the length of smoking with mortality among patients who were hospitalized in the intensive care unit (ICU) due to SARS-CoV-2 infection. This retrospective cohort study was conducted at the General Hospital in Sombor (Serbia). Patients who were hospitalized because of severe SARS-CoV-2 infection between March 2021 and March 2023 were included in this study. Data were retrieved from electronic medical records, including those on smoking status, duration of smoking, and the number of cigarettes smoked per day. Of 307 patients whose medical records were analyzed, 40.7% were current smokers. Current smokers more often required treatment in the ICU, where they also had a higher mortality rate compared to current non-smokers. Longer duration of smoking was independently associated with dying of SARS-CoV-2 infection in the ICU. The Kaplan-Meier survival curve showed that hospitalized patients with SARS-CoV-2 infection who smoked had poorer survival compared to current non-smokers. According to the receiver operating characteristic curve, patients who smoked for more than 40 years had a 73.9% chance of dying from SARS-CoV-2 infection. Current smokers who smoked 22.5 cigarettes per day had a 75.4% chance of dying from SARS-CoV-2 infection in the ICU. Smokers with severe SARS-CoV-2 infection had a higher likelihood of having poor outcomes. Longer duration of smoking was an independent predictor of SARS-CoV-2 mortality. Smoking prevention and smoking cessation are of paramount importance in the prevention of SARS-CoV-2-related mortality.